PENGARUH KAJIAN TITIK-TEMU (KTT) PADA INTERNALISASI SIKAP DAN CARA PANDANG TOLERAN MASYARAKAT: STUDI ATAS NURCHOLISH MADJID SOCIETY (NCMS) - Rahman, Fadhlu; Handayati, Evi Sri; Nuraripah, Pia (Institut Islam Nahdlatul Ulama Temanggung, 2022)
Intolerance and radicalism in Indonesia have reached a dangerous stage. The Conditions in the individual aspect affect his perspective which tends to be defensive, apologetic and pessimistic in religion. This is also the initial cause for the birth of social, political and educational implications. Islamic studies play an important role or become one of the important causes in the transfer of certain ideologies, especially intolerance. In Indonesia, studies on these ideologies are quite widespread and spread everywhere, especially the middle and lower classes in various forms of delivery variants, either through the media or directly. This of course becomes a medium for disseminating intolerant ideas which in turn lead to radical actions. This sad condition demands the existence of a counter-radical Islamic study model by carrying out the concepts of tolerance. The Summit (Meeting Point Study) promoted by the NCMS Institute (Nurcholis Madjid Society) is relevant to be appointed as the model of the study in question. This institution was specifically held to transfer the values ​​of tolerance and Islam that are rahmatan lil'alamin as promoted by Nurcholis Madjid as an icon of his character. The purpose of this study is to find out how the study transfers tolerance values ​​and at the same time examines the effectiveness of the program in terms of perspective and tolerance..